Analyzing Trends and Innovations in Solar Energy-Powered Water Pumping Systems: A Bibliometric Study on Renewable Energy Applications - Garima Dalal, Sonia, Pooja Vyas, Pooja Rani (South Eastern European Journal of Public Health, 2025)
Energy security has received significant attention in both industrialized and developing nations. During the energy transition, the use of renewable energy in electrical power networks has grown significantly. Solar photovoltaic is being acknowledged as an alternative to conventional generation sources, particularly for remote and rural locations that have isolated power infrastructures. National policies and government laws play a crucial role in promoting carbon-neutral solar photovoltaic. A bibliometric analysis was conducted on research related to solar power from 1961 to 2023 in journals covering all subject areas of the Science Citation Index to provide a deep insights the about research published in solar photovoltaic domain. The terms "solar," "solar energy," "water pump," and "water pumping system" were chosen to be searched in the title, abstract, or keywords section. The bibliometric analysis is conducted using pertinent authors, sources, words, fields, and conceptual analysis. These discoveries can help researchers and the scientific communities quickly grasp the foundational knowledge in the field of solar photovoltaic. The number of articles and citations is limited but growing, which indicates solar energy for agriculture or irrigation is a developing field and needs more contributions from researchers to enhance knowledge in this area..